Chromogenics oxides for chemical sensing - Eric Nicholas Kepawitono (2016)
Chromogenic oxides are oxide-containing materials which exhibit reversible colour changes upon contact with chemical stimuli. In this work, we will study the activity of nickel-plated films as chromogenic compounds upon chemical reactions with glucose solutions of varying concentrations and explore the repeatability of the colour changing processes involved during the reactions.